3D natural convection on a horizontal and vertical thermally active plate in a closed cubical cavity. Issue 8 (7th November 2016) - Purusothaman, Abimanyu; Baïri, Abderrahmane; Nithyadevi, Nagarajan
Abstract : Purpose: The purpose of this paper is to examine numerically the natural convection heat transfer in a cubical cavity induced by a thermally active plate. Effects of the plate size and its orientation with respect to the gravity vector on the convective heat transfer and the flow structures inside the cavity are studied and highlighted. Design/methodology/approach: The numerical code is based on the finite volume method with semi-implicit method for pressure-linked equation algorithm. The convective and diffusive terms in momentum equations are handled by adopting the power law scheme. Finally, the discretized sets of algebraic equations are solved by the line-by-line tri-diagonal matrix algorithm. Findings: The results show that plate orientation and size plays a significant role on heat transfer. Also, the heat transfer rate is an increasing function of Rayleigh number for both orientations of the heated plate. Depending on the thermal management of the plate and its application (as in electronics), the heat transfer rate is maximized or minimized by selecting appropriate parameters. Research limitations/implications: The flow is assumed to be 3D, time-dependent, laminar and incompressible with negligible viscous dissipation and radiation. The fluid properties are assumed to be constant, except for the density in the buoyancy term that follows the Boussinesq approximation. Originality/value: The present work will give some additional knowledge in designing sealed cavities encountered in some engineering applications as in aeronautics, automobile, metallurgy or electronics.